Allocation of European structural funds and strategic interactions: is there a yardstick competition between regions in the public aid for development? - Lionel Vedrine (European Regional Science Association (ERSA), 2012)
This paper analyzes the relationships between the degree of decentralization of public policy and the emergence of horizontal strategic interactions. We analyze the structural funds allocation process in determining how the structure of governance of cohesion policy a ects the development of strategic interactions between regional governments. We develop a political agency model in which we capture the e ect of the governance structure of public policy on the decision of voters to acquire information on the activities of local governments. We show that the appearance of spatial interactions resulting from a mechanism of 'yardstick competition' is increasing with the degree of policy decentralization. From an empirical analysis of the 2000-06 period, we con firm the proposed model by showing that spatial interactions are more intense when the policy governance is decentralized. This work highlights a new source of spatial interaction in the allocation of grants from institutional determinants in addition to socioeconomic factors studied so far.
Keywords: C31; C71; D86; H77; 330; Intergovernmental grant allocation; European Union; Political agency; Yardstick competition; Information acquisition; Spatial econometrics